2018
DOI: 10.7759/cureus.3001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Among Nurses in Pakistan Towards Diabetic Foot

Abstract: IntroductionDiabetic foot ulcers are a pressing complication of diabetes mellitus. Wound care requires a significant proportion of healthcare resources. It is imperative, therefore, for healthcare professionals to possess sound knowledge of the disease along with a positive attitude to ensure better clinical practice. Our literature search revealed a scarcity of data pertaining to diabetic foot ulcers. Therefore, this study aims to evaluate the knowledge and attitudes of nurses regarding diabetic foot care.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 17 publications
5
35
2
2
Order By: Relevance
“…Diabetes mellitus (DM) is now becomes a global health issue to health care professionals 1. According to International Diabetes Federation (IDF) 451 million (age 18-99 years) people was reported with diabetes worldwide 415 million people in 2017, which expected to increase to 693 million) in 2045 2. Approximately 7.5 million Pakistani people suffer from DM 3.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is now becomes a global health issue to health care professionals 1. According to International Diabetes Federation (IDF) 451 million (age 18-99 years) people was reported with diabetes worldwide 415 million people in 2017, which expected to increase to 693 million) in 2045 2. Approximately 7.5 million Pakistani people suffer from DM 3.…”
Section: Introductionmentioning
confidence: 99%
“…Similar data for the nurses' knowledge assessment were found in a study conducted in Pakistan, which revealed that 13.0% and 15.0% of the nurses had very low or low knowledge, respectively, and only 14.0%. % of participants had high levels of knowledge about diabetic ulcer care, 14 reaffirming the need for training in the area to improve care for people with diabetes in Primary Health Care.…”
Section: Resultsmentioning
confidence: 78%
“…The PUKAT took approximately 30 minutes 44,56 . Kumarasinghe's 56 instrument was pilot‐tested and considered to be feasible 56,57 …”
Section: Resultsmentioning
confidence: 99%